Analisis Penerapan Artificial Intelligence terhadap Produktivitas Perusahaan Media Informasi - Saputra, Raihan; Mahaputra, M. Rizky; Saputra, Farhan; Mahaputra, M. Ridho (Jurnal Pendidikan Siber Nusantara, 2023)
This research discusses the analysis of the application of artificial intelligence to the productivity of information media companies. Where this research examines previous research to support the problem formulation. A qualitative research approach was applied. Data was obtained from internet sources such as Google Scholar, Mendeley, DOAJ, and EBSCO. The results of this research include: 1) The application of Artificial Intelligence affects the productivity of information media companies: where Artificial Intelligence will make employee work easier, so that the workload given by the company will be completed easily and quickly by employees; 2) The use of Artificial Intelligence affects the quality of the content produced: where information media companies are closely related to content, including videos, photos and so on; 3) Challenges faced by companies in implementing Artificial Intelligence in their operational activities: where human resources are not yet accustomed to using AI optimally; and 4) Employees' response to the application of Artificial Intelligence in the company: they feel interested, motivated, and want to know more about the application of AI in their company. But there are some employees who consider AI a threat to them and think it will replace their jobs